Vitamin E and carotenoid profiles in leaves, stems, petioles and flowers of stinging nettle (Urtica leptophylla Kunth) from Costa Rica. (23rd May 2022) - Montoya‐Arroyo, Alexander; Toro‐González, Camilo; Sus, Nadine; Warner, Jorge; Esquivel, Patricia; Jiménez, Víctor M; Frank, Jan
Abstract: BACKGROUND: Local leafy vegetables are gaining attention as affordable sources of micronutrients, including vitamins, pro‐vitamin carotenoids and other bioactive compounds. Stinging nettles ( Urtica spp.) are used as source of fibers, herbal medicine and food. However, despite the relatively wide geographical spread of Urtica leptophylla on the American continent, little is known about its content of vitamin E congeners and carotenoids. We therefore investigated the particular nutritional potential of different plant structures of wild Costa Rican U. leptophylla by focusing on their vitamin E and carotenoid profiles. RESULTS: Young, mature and herbivore‐damaged leaves, flowers, stems and petioles were collected and freeze‐dried. Vitamin E and carotenoids were determined by high‐performance liquid chromatography after liquid/liquid extraction with hexane. α‐Tocopherol was the major vitamin E congener in all structures. Flowers had a high content of γ‐tocopherol. Herbivore‐damaged leaves had higher contents of vitamin E than undamaged leaves. Lutein was the major and β‐carotene the second most abundant carotenoid in U. leptophylla . No differences in carotenoid profiles were observed between damaged and undamaged leaves. CONCLUSION: The leaves of U. leptophylla had the highest nutritional value of all analyzed structures; therefore, they might represent a potential source of α‐tocopherol, lutein and β‐carotene. © 2022 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.